New Metabolites Produced by Cylindrocarpon sp. SY‐39 from a Driftwood. Issue 2 (31st January 2018) - Suzuki, Takuma; Yoshida, Seiya; Koseki, Takuya; Aboshi, Takako; Murayama, Tetsuya; Supratman, Unang; Shiono, Yoshihito
Abstract : Four novel compounds, cylindropyrone A (1 ), 10′‐hydroxyilicicolinic acid D (3 ), cylindrolactones A (4 ) and B (5 ), together with known dihydroinfectopyrone (2 ) were isolated from the culture of Cylindrocarpon sp. SY‐39 from a driftwood. Their structures were elucidated using 1D‐ and 2D‐NMR spectroscopy. Compound3 showed antimicrobial activity against Staphylococcus aureus with MIC value of 5.0 μg/mL. Abstract :